Impact of Body Mass Index and Discomfort on Upper Airway Stimulation: ADHERE Registry 2020 Update. (19th July 2021) - Suurna, Maria V.; Steffen, Armin; Boon, Maurits; Chio, Eugene; Copper, Marcel; Patil, Reena Dhanda; Green, Katherine; Hanson, Ronald; Heiser, Clemens; Huntley, Colin; Kent, David; Larsen, Christopher; et al.
Abstract : Objectives/Hypothesis: To provide the ADHERE registry Upper Airway Stimulation (UAS) outcomes update, including analyses grouped by body mass index (BMI) and therapy discomfort. Study Design: Prospective observational study. Methods: ADHERE captures UAS outcomes including apnea‐hypopnea index (AHI), Epworth sleepiness scale (ESS), therapy usage, patient satisfaction, clinician assessment, and safety over a 1‐year period. BMI ≤32 kg/m 2 (BMI32 ) and 32 < BMI ≤35 kg/m 2 (BMI35 ) group outcomes were examined. Results: One thousand eight hundred forty‐nine patients enrolled in ADHERE, 1, 019 reached final visit, 843 completed the visit. Significant changes in AHI (−20.9, P  < .0001) and ESS (− 4.4, P  < .0001) were demonstrated. Mean therapy usage was 5.6 ± 2.2 hr/day. Significant therapy use difference was present in patients with reported discomfort versus no discomfort (4.9 ± 2.5 vs. 5.7 ± 2.1 hr/day, P  = .01). Patients with discomfort had higher final visit mean AHI versus without discomfort (18.9 ± 18.5 vs. 13.5 ± 13.7 events/hr, P  = .01). Changes in AHI and ESS were not significantly different. Serious adverse events reported in 2.3% of patients. Device revision rate was 1.9%. Surgical success was less likely in BMI35 versus BMI32 patients (59.8% vs. 72.2%, P  = .02). There was a significant therapy use difference: 5.8 ± 2.0 hr/day in BMI32 versus 5.2 ± 2.2 hr/day in BMI35 ( P  = .028). Conclusions: Data from ADHERE demonstrate high efficacy rates for UAS. Although surgical response rate differs between BMI32 and BMI35 patient groups, the AHI and ESS reduction is similar. Discomfort affects therapy adherence and efficacy. Thus, proper therapy settings adjustment to ensure comfort is imperative to improve outcomes. Level of Evidence: 4 Laryngoscope, 131:2616–2624, 2021